Prevalence and risk factors for respiratory symptoms among children at child care centers in Malaysia - Abdul Malik, Abdul Malik (Bellwether Publishing, Ltd., 2020)
Many studies have been conducted to assess the effects of indoor air quality (IAQ) on human health. However, there is still a lack of studies available about the adverse health effects on children’s respiratory health at Child Care Centers (CCC). The aim of this paper was to investigate the risk factors for respiratory symptoms and identify the root cause of IAQ problems at CCCs in Malaysia. The Modified American Thoracic Society and the Division of Lung Diseases (ATS-DLD-82) questionnaire was used to gather information from parents regarding their children’s respiratory symptoms. The IAQ parameters measured were for air temperature, humidity, carbon dioxide, carbon monoxide, respirable particles (PM2.5), viable bacteria and fungi count while the information on CCC characteristics and potential surrounding air pollutants were collected via a combination of area monitoring, inspection and interviews. Factors found to be significantly associated with persistent cough and/or cold were age, type of ventilation, location of CCC, floor area per child (<3.5m2) and temperature. Children attending CCCs supplied by ACMV had the highest risk for prevalence of persistent productive cough [5.56 (CI: 2.20; 14.00)]. This study provided the baseline data on IAQ and possible factors that influenced indoor air contaminants, which could aid policy makers in formulating guidelines on IAQ for CCC in Malaysia.